PENGARUH PERCEIVED QUALITY DAN CUSTOMER SATISFACTION TERHADAP REPURCHASE INTENTION MELALUI BRAND PREFERENCE SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Hayfa Beauty Skin Care Semarang Cabang Tlogosari) - Nisrina Kamilah; Naili Farida (Universitas Diponegoro, 2016)
This research is motivated by the fluctuations of Hayfa BSC Tlogosari Semarang’s revenues. Hayfa BSC’s total revenue has not reached the target, despite demand increasing for beauty clinic. The purpose of this study was to determine the effect of perceived quality and customer satisfaction on repurchase intention through brand preference on Hayfa BSC Tlogosari Semarang. This type of research is explanatory research with data collection through questionnaires and interviews. Samples in this study are 100 respondents, who are the customers of Hayfa BSC Tlogosari Semarang. The sampling technique used purposive sampling technique. This study uses qualitative and quantitative analysis techniques. Quantitative analysis using validity test, reliability test, the coefficient of correlation test, simple and multiple regression analysis, coefficient of determination test, significance test (t test) in one direction, two-stage regression, and Sobel test using Preacher's Tool. The results showed a positive effect of perceived quality and customer satisfaction on brand preference partially, and brand preference has positive influence on repurchase intention. The two stages regression analysis showed that the perceived quality and consumer satisfaction influence the brand preference, each coefficient is 0,438 and 0,287. Brand preference affect the repurchase intention with the coeffiecient of 0.709. Based on Sobel test, brand preferences act as a partial mediating variable.